Predicting Foreign Firms' Expansion and Divestment Intentions in Host Countries: Insights from Ghana. (4th April 2014) - Nyuur, Richard B.; Debrah, Yaw A.
<x xml:space="preserve">Abstract</x> Foreign firms' strategic decisions in a host country after the initial investment are important issues worth extensive academic enquiry. This issue is, however, underresearched and the scant literature that does exist is focused on developed countries, despite the increasing interests and investments by firms in developing countries. Using the case of a developing sub‐Saharan African (SSA) country (Ghana), this study attempts to close this gap in the literature, as it explores the factors that can influence foreign firms' strategic decisions regarding expansion, downsizing, relocation and termination of their operations. The study found that host countries' business environments play an important role in foreign firms' subsequent strategic decisions. The study particularly found that favorable government regulations, low cost factors and good infrastructure are important in influencing foreign firms' expansions decisions. Unfavorability of these factors within the business environment on the other hand will stimulate strategic divestment. © 2014 Wiley Periodicals, Inc.